DIDACTIC TEACHING AS A PATHWAY TO ACADEMIC SUCCESS: EVALUATING ITS INFLUENCE IN EDUCATION - Jennings, Thomas Edward; Foster , David William (Research Journal of Education and Allied Studies, 2024)
The effectiveness of teaching methods in influencing learning outcomes is a critical concern in education, yet it often lacks empirical support. This paper addresses this gap by investigating the association between teaching methods and educational outcomes in English secondary schools. Through a thorough literature review, diverse perspectives on teaching methodologies and their potential impact on student achievement are explored. The study utilizes data from a cohort of secondary schools, detailing the methodology and scope of research. Employing rigorous statistical analysis, the paper examines the relationship between teaching methods and students' academic performance, providing valuable insights into effective pedagogical practices. The findings of the analysis are discussed, highlighting implications for educational practice and policy. By bridging theory and practice, this study aims to inform educators, policymakers, and stakeholders about the efficacy of different instructional approaches in secondary education.